2019
DOI: 10.3390/app9122392
|View full text |Cite
|
Sign up to set email alerts
|

Study of Dynamic Response Characteristics of the Wind Turbine Based on Measured Power Spectrum in the Eyewall Region of Typhoons

Abstract: The present research envisages a method for calculating the dynamic responses of the wind turbines under typhoon. The measured power spectrum and inverse Fourier transform are used to generate the fluctuating wind field in the eyewall of the typhoon. Based on the beam theory, the unsteady aerodynamic model and the wind turbine dynamic model are coupled to calculate the dynamic response. Furthermore, using this method, the aeroelastic responses of a 6 MW wind turbine at different yaw angles are studied, and a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As a case study of a WT under typhoon conditions, a commercial 6 MW offshore WT was selected, the main parameters of which are listed in Table 2 [25]. The simulation range of the WT inflow wind speed field is 200 m × 200 m, which is divided into 256 nodes covering the entire wind wheel plane, as shown in Figure 4.…”
Section: Wind Turbine Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As a case study of a WT under typhoon conditions, a commercial 6 MW offshore WT was selected, the main parameters of which are listed in Table 2 [25]. The simulation range of the WT inflow wind speed field is 200 m × 200 m, which is divided into 256 nodes covering the entire wind wheel plane, as shown in Figure 4.…”
Section: Wind Turbine Modelmentioning
confidence: 99%
“…Dong et al [24] reported that WT blades are more susceptible to vibration and instability caused by low-frequency excitation under yawing conditions. In [25], the ultimate load characteristics of 40 m/s applied to WTs at different yaw angles were studied. It was found that the load on the tower exceeded the design limit load at inflow angles of 30 and 120 degrees.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it diagnoses faults in the field-oriented control of doubly fed induction generators (DFIG) using frequency spectrum and Lissajous curves [6]. Han et al [7] combined the unstable streamlined and WT dynamic models to compute a unique response based on beam theory in a typhoon for 6 MW and 2 MW WTs. Meanwhile, Rolán and Pedra [8] proposed a calculation to investigate DFIG WT.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in terms of the impact of typhoons on the overall performance of wind turbines, Ran Han [17] studied the dynamic response of 2 MW and 6 MW wind turbines at different yaw angles based on the blade element momentum theory and multi-body dynamics. The results show that the tip deflection reaches its maximum when the yaw angle is between 30 • and 120 • , and this conclusion is universal.…”
Section: Introductionmentioning
confidence: 99%